Analyzing Students’ Ability in Using the Language Features in Writing Descriptive text - Bela Putri Mendale; Endang Komariah; Siti Sarah Fitriani (Research in English and Education Journal, 2020)
The purpose of this research was to find out the students’ ability in using the language feature in writing descriptive text. This research was designed as quantitative research and it was conducted at SMPN 4 Banda Aceh is located at Peunayong on April 25th 2019. The number of sample in this research was 20 students which were taken from the seven grade students. In this research, the researcher used writing test as the instrument of the research where the students were asked to write the language features in a descriptive text based on the picture given to them. In this research, the researcher analyzed two components of descriptive text written by the students such as grammar and vocabulary. To measure students’ ability, the researcher showed the result that in the grammar analysis of writing, 20% of the students score 22-25, 60% score 19-21, and 20% score 11-17. In the result vocabulary analysis 75% score 18-20 and 25% score 14-17. The result level categories of vocabulary 75% level excellent. 25% level good. And the result level categories of grammar 20% level excellent, 60% level good the last 20% level fair. From the result it means their ability in using the language features in writing descriptive text can be categorized in the good level.